Analisis Kelengkapan Catatan Rekam Medis Kasus Tetralogy of Fallot pada Implementasi INA-CBGS di RSPJN Harapan Kita - Sakidjan, Indriwanto (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2014)
This qualitative study discusses the inaccuracies on medical record entry charging, and inaccuracy on coding that caused provider bear the financial risk in the case of Tetralogy of Fallot in INA-CBG at the Pediatric Cardiology and congenital heart disease unit RS Harapan Kita from January-September 2013. This study showed that 21.4% of cases with incomplete secondary diagnosis and the difference between the claim of Rp 251.273.615,- (4%). Factors contributed incomplete secondary diagnoses are: responsiblity, physical facilities, standard operating procedure of medical record, training, monitoring, and socialization. Therefore, tt is recommended to improve: physical facilities, structure and infra-structure, standard operating procedure of medical record, socialization, training and monitoring at regular intervals